"Sponsorshipped": Reflections on temporary female migration from the Horn of Africa to the Gulf and Lebanon - Ramos, Manuel João (2017)
Female migratory flows from the Horn of Africa are mainly directed to Arab countries and tend to take the form of temporary legal migration. Like their Asian counterparts, these girls and women are subject to varying degrees of trafficking and even enslavement, working mainly as in-house maids in affluent Arab households, where they tend to be denied free and fair labour rights, under a harsh interpretation of the kafala, or "sponsorship" system, prevalent in Arabic countries. Although there are signs of better legal protection under international labour rules, the system in place and the culture that supports it impose a tense situation where maids are subject to everyday “structural violence” and employers have to bear an unwonted responsibility. The psychological, social and economic costs of this migration are well documented but there's still a lack of understanding of the trends of female agency that emerges as a direct reflection of the hardships of such forms of migration. This chapter reflects on the ways this situation is understood and managed in the hosting countries.